The Influence of Live-Streaming Commerce and Brand Recognition on The Intention to Purchase the Erigo Brand - Matovani, Satria Rafi Athaullah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to examine the effect of live-streaming commerce and brand recognition on the intention to purchase the “Erigo” brand through the TikTok live shopping. The background of this study is the advancement of technology in marketing, enabling business actors to utilize new media in promotional activities, specifically live-streaming commerce on TikTok. The sample of this causal quantitative study comprised 190 Erigo consumers in Malang City, East Java, selected using a non-probability sampling method. The results of the multiple linear regression analysis indicate that live-streaming commerce and brand recognition have a significant and positive effect on purchase intention. Thus, live-streaming commerce and brand recognition enhance the purchase intention of Erigo brand consumers in Malang City. Additionally, live-streaming commerce has a dominant influence on the purchase intention of Erigo products, suggesting that Erigo consumers in Indonesia are inclined to make purchases while watching live shopping sessions on TikTok. Based on these findings, the Erigo company is expected to be more responsive to technological advancements in marketing and leverage social media to boost product sales.